Aloe-emodin prevents nerve injury and neuroinflammation caused by ischemic stroke via the PI3K/AKT/mTOR and NF-κB pathway. Issue 17 (20th July 2021) - Xian, Minghua; Cai, Jiale; Zheng, Kening; Liu, Qu; Liu, Yali; Lin, Huiting; Liang, Shengwang; Wang, Shumei
Abstract : Study of the protective role of aloe-emodin in nerve injury and neuroinflammation in vivo and in vitro, to provide a scientific basis for aloe-emodin treatment of neurological diseases. Abstract : Ischemic stroke (IS) caused by cerebral arterial occlusion is the leading cause of global morbidity and mortality. Cellular oxidative stress and inflammation play a vital role in the pathological process of neural damage in IS. It is necessary to develop functional food or drugs, which target neuroinflammation and oxidation mechanisms against IS. The molecule compound aloe-emodin (AE) is derived from aloe and rhubarb. However, the exact mechanism of the pharmacological action of AE on IS remains unclear. Here, for aiming to demonstrate the mechanism of AE, our study explored the middle cerebral occlusion reperfusion (MCAO/R) rats in vivo, oxygen and glucose deprivation reperfusion (OGD/R), and lipopolysaccharide (LPS)-stimulated cells in vitro . We found that AE significantly improved the infarct size and behavioral score of MCAO/R rats, decreased the expression of TNF-α, MDA, LDH, Caspase 3, and increased the expression of SOD, Bcl-2/Bax. Liquid chromatography-mass spectrometry (LC/MS) results showed that AE could penetrate the blood–brain barrier in the sham group and MCAO/R group. In vitro, AE significantly protected SH-SY5Y cells from the insult of OGD/R and reduced the production of inflammatory cytokines in BV2 cells stimulated by LPS. In vivo and in vitro, western blot analysis results showed that AE significantly increased the expression of PI3K, AKT and mTOR proteins. In addition, AE significantly decreased NF-κB protein expression in BV2 cells. The use of AKT-specific inhibitor MK-2206 2HCL to inhibit AKT expression can block the protective effect of AE on SH-SY5Y cells subjected to OGD/R insults. Overall, our study suggests that AE protected against cerebral ischemia-reperfusion injury probably via the PI3K/AKT/mTOR and NF-κB signaling pathways. Thus, these results indicated that AE could be a promising first-line therapy for preventing and treating ischemic stroke and can be used as functional food.